Impact of neutrino oscillations on the r-process in different astrophysical scenarios - Sáez, María Manuela (2021)
In this work, we studied the production of heavy-mass elements, through the rapid neutron-capture mechanism (r-process), associated with different astrophysical scenarios. Since the r-process consists on captures of neutrons followed by /3-decays, if sterile neutrinos exist, a reformulation of the weak-decay rates due to the presence of massive neutrinos and sterile neutrinos, is needed. These rates are used to compute the abundances of the heavy elements produced in core-collapse supernova and neutron-star mergers and then ejected to the interstellar medium. We show how the abundances are affected if the active-sterile neutrino oscillations are considered in the formalism. We found that the best agreement between theoretical and experimental data is given when active-sterile neutrino mixing angle is sin2 (2^14) = 0.23 and when the neutron-star merger environment is dominant (about 70% of the production of the total heavy nuclei abundance).